Implementation of Islamic Boarding School Accounting Guidelines to Increase Accountability and Welfare of Islamic Boarding Schools in Semarang City - Asrori Asrori; Muhammad Ihlashul'amal; Kuat Waluyo Jati (Indonesian Journal of Devotion and Empowerment, 2023)
The purpose of this community service is to improve the ability and competence of board members and managers of Islamic boarding schools to implement the Islamic Boarding School Accounting Guidelines in preparing and presenting financial reports in order to increase accountability for financial management and the welfare of the stakeholders of Islamic boarding schools in the city of Semarang. The results achieved from this Community Service are that the competency of the pesantren accounting training participants, in general, has increased, especially regarding their literacy regarding Islamic boarding school accounting, including the types and uses of Islamic boarding school financial reports, and their ability to analyze and record Islamic boarding schools transactions in journals. However, the competency of the participants in compiling and presenting PAP-based Islamic boarding school financial reports in the form of Activity Reports and Cash Flow Reports is still weak, not yet fully following the guidelines and accounting standards of Islamic boarding schools and generally accepted accounting standards in Indonesia imposed by the Indonesian Institute of Accountants (IAI) for Pondok Pesantren in the form of a Foundation. As a follow-up to this Community Service, it is necessary to carry out further Community Service to increase the accountability of Islamic boarding schools by preparing and presenting more in-depth financial reports through Islamic boarding school accounting assistance to increase accountability and welfare for Islamic boarding schools in the city of Semarang. Tujuan pengabdian kepada masyarakat ini adalah untuk meningkatkan kemampuan dan kompetensi pengurus dan pengelola pondok pesantren mengimplementasikan Pedoman Akuntansi Pesantren dalam Menyusun dan menyajikan laporan keuangan guna meningkatkan akuntabilitas pengelolaan keuangan dan kesejahteraan para memangku kepentingan pondok pesantren di Kota Semarang. Hasil yang dicapai dari pengabdian ini adalah kompetensi peserta pelatihan akuntansi pesantren secara umum meningkat, terutama menyangkut literasi mereka mengenai akuntansi pesantren meliputi jenis-jenis dan kegunaan laporan keuangan pesantren, dan kemampuannya menganilisis dan mencatat transaksi pesantren ke dalam jurnal. Namun demikian kompetensi peserta dalam menyusun dan menyajikan laporan keuangan pesantren berbasis PAP dalam bentuk Laporan Aktivitas dan Laporoan Arus Kas masil lemah, belum sepenuhnya seuai dengan pedoman dan standar akuntansi pesantren dan standar akuntansi berterima umum di Indonesia yang diberlakukan oleh Ikatan Akuntan Indonesia (IAI) bagi Pondok Pesantren berbentuk Yayasan. Tidak lanjut dari pengabdian ini adalah perlu dilakukan pengabdian lanjutan untuk meningkatkan akuntabilitas pondok pesantren dalam penyususunan dan penyajian laporan keuangan pesantren yang lebih mendalam melalui pendampingan akuntansi pesantren untuk meningkatkan akuntabilitas dan kesejahteraan bagi pondok pesantren di Kota Semarang.